2020
DOI: 10.1111/pan.13987
|View full text |Cite
|
Sign up to set email alerts
|

Association between preoperative hemoglobin levels after iron supplementation and perioperative blood transfusion requirements in children undergoing scoliosis surgery

Abstract: Background and Aims: In this study, we assessed the association between preoperative hemoglobin and red blood cell transfusion in children undergoing spine surgery after the implementation of our preoperative iron supplementation protocol. Method: We performed a retrospective analysis of patients who underwent posterior spinal fusion surgery between January 2013 and December 2017 and received preoperative iron supplementation. We used uni-and multivariable logistic regression to determine the association betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Two studies suggest that higher preoperative hemoglobin levels as a result of iron supplementation lead to the need for fewer transfusions in pediatric patients undergoing posterior spinal fusion. 45,46 Typical regimens include 325 mg (65 mg elemental iron) of ferrous nitrate twice per day for 4 weeks preoperatively. Preoperative erythropoietin has also been studied as a blood conservation strategy.…”
Section: Error Trap 3: Failure To Prevent Excessive Bleeding Decrease...mentioning
confidence: 99%
“…Two studies suggest that higher preoperative hemoglobin levels as a result of iron supplementation lead to the need for fewer transfusions in pediatric patients undergoing posterior spinal fusion. 45,46 Typical regimens include 325 mg (65 mg elemental iron) of ferrous nitrate twice per day for 4 weeks preoperatively. Preoperative erythropoietin has also been studied as a blood conservation strategy.…”
Section: Error Trap 3: Failure To Prevent Excessive Bleeding Decrease...mentioning
confidence: 99%
“…It is, therefore, critical to optimise haemoglobin level and coagulation profile preoperatively, with consultation with haematological specialists, and consideration of iron supplementation or recombinant erythropoietin [ 15 , 16 ]. During the positioning of patients prone for surgery, the abdomen must be kept free from direct pressure to avoid increased venous pressure in vertebral vessels and risk of increased intraoperative bleeding within the surgical field [ 17 ].…”
Section: Intraoperative Complicationsmentioning
confidence: 99%
“…In this case, intravenous iron has the advantage over oral iron in overcoming this barrier and thereby achieve effective erythropoiesis. Previous studies have shown promising results for the use of intravenous iron therapy in patients after spinal deformity surgery but still lacking standard practice 9…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown promising results for the use of intravenous iron therapy in patients after spinal deformity surgery but still lacking standard practice. 9 …”
Section: Introductionmentioning
confidence: 99%